Recent Progress in the Medicinal Chemistry of γ-Secretase Inhibitors - Olson, Richard E.; Albright, Charles F. (Current Topics in Medicinal Chemistry, 2008)
Aβ is implicated in the initiation and progression of Alzheimer's disease (AD) by the phenotypic analysis of mutations in three human genes that lead to inherited, early forms of AD and data from preclinical studies. Based on this evidence, γ-secretase inhibitors are being actively pursued as potential AD therapeutics to reduce Aβ formation. This manuscript reviews recent progress in the medicinal chemistry of three major classes of γ-secretase inhibitors: peptide isosteres, azepines, and sulfonamides. Peptide isosteres have been useful for demonstrating that presenilin is the catalytic subunit of γ-secretase and probing the active site. The peptidic nature of these inhibitors has, however, interfered with their utility for in vivo studies. Instead, the pharmaceutical industry has focused on optimizing azepines and sulfonamides. Both azepines and sulfonamides bind to a common, allosteric site on presenilin that differs from the active site identified by the peptide isosteres. Significant progress in the optimization of both azepines and sulfonamides has led to compounds that inhibit brain Aβ synthesis in preclinical models and has culminated in the identification of γ-secretase inhibitors, including LY- 450139 and MK-0752, for human trials.